1985
DOI: 10.1042/bj2290073
|View full text |Cite
|
Sign up to set email alerts
|

Turnover of messenger RNA, apoprotein and haem of cytochrome P-450b + e induced by phenobarbitone in rat liver

Abstract: A single injection of phenobarbitone elicits asynchronous behaviour in the pattern of induction of mRNA, apoprotein and haem of cytochrome P-450b + e. The mRNA content reaches a maximum around 16h, the apoprotein content reaches a maximum around 30-36h, and the holoprotein content shows biphasic behaviour, with maxima around 16h and 30-36h. With the use of CoCl2 to block fresh transcription of cytochrome P-450b + e mRNA, the half-life of the preinduced mRNA was found to be 3h. The apoprotein and haem moieties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…added P-450b/e gene fragment, and the result correlates well with changes in P-450b/e mRNA levels in vivo and run-on transcription rates in vitro reported earlier (8,10). Because transcription of the added gene fragment should involve fresh initiation, the upstream sequence (from position -179) probably has sites for interaction with protein factors modulating transcription of P450b/e genes.…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…added P-450b/e gene fragment, and the result correlates well with changes in P-450b/e mRNA levels in vivo and run-on transcription rates in vitro reported earlier (8,10). Because transcription of the added gene fragment should involve fresh initiation, the upstream sequence (from position -179) probably has sites for interaction with protein factors modulating transcription of P450b/e genes.…”
Section: Resultssupporting
confidence: 64%
“…(ii) Effects of these inhibitors can be counteracted by exogenous hemin. (iii) Changes in the mRNA levels in vivo correlate with their run-on transcription rates with nuclei isolated from treated rat livers (7)(8)(9)(10). In addition, we have also shown that cycloheximide, a translation inhibitor, specifically blocks the transcriptional activation of P-450b/e and -c/d genes by phenobarbitone and 3-MC, respectively (11).…”
mentioning
confidence: 99%
“…Earlier studies from this laboratory have shown that CoCl 2 treatment leads to a striking decrease in the heme pool (13)(14)(15)(16). The present study has also made use of this reagent to precipitate heme deficiency.…”
Section: Resultsmentioning
confidence: 97%
“…Earlier studies from this laboratory have also implicated that heme, the prosthetic group of cytochrome P-450, is a positive modulator of CYP2B1/B2 gene transcription (13)(14)(15)(16)). This conclusion is based on the fact that inhibitors of heme biosynthesis block induction of CYP2B1/B2 mRNA by PB and its run-on transcription in isolated nuclei.…”
mentioning
confidence: 99%
“…5 A shows that only PB induced these mRNA. Maximal induction with PB was attained by [16][17][18][19][20][21][22][23][24] h, as was previously…”
Section: Quantitative Assessmentmentioning
confidence: 99%